2000
DOI: 10.1063/1.1309023
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-layer growth of GaN induced by silicon

Abstract: We present in situ x-ray scattering studies of surface morphology evolution during metal–organic chemical vapor deposition of GaN. Dosing the GaN(0001) surface with Si is shown to change the growth mode from step-flow to layer-by-layer over a wide temperature range. Annealing of highly doped layers causes Si to segregate to the surface, which also induces layer-by-layer growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 15 publications
3
18
0
Order By: Relevance
“…This reaction occurs only at elevated temperatures and is not present during low temperature seed layer growth even when GaN is grown at low temperatures directly on Si. Si outdiffusion from the substrate through the growing layer is assumed to cause the poor morphology [21,22] since high Si concentrations lead to a deteriorated GaN growth and rough surfaces [23,24]. We observed that cracking or particles can also initiate the etching reaction.…”
Section: Introductionmentioning
confidence: 81%
“…This reaction occurs only at elevated temperatures and is not present during low temperature seed layer growth even when GaN is grown at low temperatures directly on Si. Si outdiffusion from the substrate through the growing layer is assumed to cause the poor morphology [21,22] since high Si concentrations lead to a deteriorated GaN growth and rough surfaces [23,24]. We observed that cracking or particles can also initiate the etching reaction.…”
Section: Introductionmentioning
confidence: 81%
“…75 It has also been suggested that Si induces roughness 76 and cracks, 77 and it might segregate at the surface. 78 This degradation of the layers has been attributed to the formation of Si 3 N 4 precipitates when the layers are deposited under N-rich conditions. 79 In our case, for thick GaN or Al x Ga 1−x N ͑x Յ 0.65͒ layers grown by PAMBE under Ga-rich conditions, we do not observe any perturbation of the Ga kinetics during GaN growth in presence of Si.…”
Section: Effect Of Si Dopingmentioning
confidence: 99%
“…Because the island shape is controlled by step edge energy, the surfactant behavior of dopants such as Si may have a large effect on the surface morphology. 18 See supplementary material for additional discussion of the experimental methods and data fitting. …”
mentioning
confidence: 99%